173 Experience with concurrent chemoradiotherapy treatment in advanced cervical cancer: results of a hospital in argentina. (18th September 2019) - Giavedoni, ME; Lucas, S; Rosa, G; Cintia, B; Mabel, S; Perrotta, M
Abstract : Objectives: Describe our experience with concurrent chemoradiotherapy (CCRT) using three- dimensional conformal pelvic radiotherapy (3D-CRT) and high dose rate intracavitary brachytherapy (HDR-ICBT) with weekly cisplatin in the treatment of patients with local advanced uterine cervical cancer. Methods: Forty tree patients were identified between January 2009 and December 2015. We retrospectively reviewed their medical records and data on patients' characteristics, tumor, treatment and toxicities were collected and analyzed. Results: The median age was 45 years old (IR: 26). The median tumor size was 45 mm (IR: 20). Thirty-eight patients (88%) had cervical tumor size ≥40 mm. The median cervical tumor size assessed by MRI was 52 mm (IR: 17). Twenty-two patients (51%) had enlarge nodes on MRI (≥10 mm). The MRI showed involvement of the parametrium in twenty-nine patients (67%). Fifteen patients had positives paraaortic nodes (36%). The median overall treatment time was 58 days (RI: 20). Seventeen patients (39%) received extended field radiotherapy. Cisplatin was concurrent administered for a median of 5 courses. The median follow up period was 32 months (IR: 28 months). Acute gastrointestinal grade 3 toxicity was observed in seven patients (16%). Late grade 3/4 toxicity was observed in fourteen patients (33%). Seven patients (16%) persisted with disease and five of them died. The local relapse rate was 9%. Eleven patients underwent hysterectomy after treatment. The disease free interval was 24, 2 months. The actuarial 2-year overall rate was 82, 9%. Conclusions: Concurrent chemoradiotherapy appears to be effective regimen for patients with local advanced cervical cancer with acceptable toxicity.